Geriatric Medicine and Gerontology - Zawada, Edward T. Jr (IntechOpen, 2019)
This volume is a collection of reports dealing with geriatrics and gerontology. The first section provides an introduction to the common medical and non-medical problems of aging. The second section concentrates on one of the most devastating problems of the elderly, that of dementia. Finally, the third section deals with newer topics such as hearing loss, acute and chronic lymphoproliferative disorders, and the use of nerve and muscle stimulation to reduce morbidity and mortality associated with degenerative neurologic diseases. The chapters contained herein represent the transformation of managing older patient problems that commonly impact quality of life after the age of 60 years.